(untitled) (Research, Society and Development, 2020)
The Internet of Things has unveiled to be a potentially disruptive technology in different fields of human activity which includes educational processes. The processing of data produced and stored by everyday objects captured and processed on the web can potentiate the educator´s pedagogical analyses and in terms provide them with more freedom to intervene in the formative resources of the students. Despite all the research related to IoT and education it is in initial stages and does not provide a clear vision of developing such potential. This article introduces a systematic literature review to better show the possibilities of connection between IoT, and education by gathering data and analyzing the content of it, clustering it by year, and country of publication, context and education level, study focus, adopted technologies, methodological, and theorical aspects, and development of competencies by such technologies. Most research was focused on technical and useful aspects of IoT, however there are proposals with theorical and methodological frames of reference with a pedagogical character. These results show the need to go beyond the interconnection between IoT and education, and also the possibilities of future research and the areas that should be looked into as to making it possible to use that technological potential for the promotion of new approaches in the teaching and learning areas.